INTERNATIONAL ENVIRONMENTAL GOVERNANCE REFORM WITHIN THE UNITED NATIONS: SEEKING MORE SUSTAINABILITY TOWARDS AND BEYOND RIO + 20 EARTH ENVIRONMENT SUMMIT - Manga, Sylvestre-José-Tidiane (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2010)
The International Environmental Governance reform expected soon within the United Nations system is the main point of the 2012 Rio + 20 Summit Agenda. The challenge, as currently presented by the Consultative Group of Ministers on IEG, is to lay down the foundation leading to the establishment of a World Environment Organization able to produce efficiency in the coordination of the multitude of agencies which now belong to UNEP. This paper acknowledges the achievements of the Consultative Group of Ministers. It aims however to show that such an administrative reform may be able to improve IEG in terms of administration efficiency and accountability but has unfortunately a very limited effect in ensuring enough sustainability towards and beyond Rio + 20. It is therefore suggested the creation of a WEO with two key bodies able to bring in more sustainability. The first body is the WEO Scientific Body. Its mandate will be to measure and adopt sustainable standards, rates and limits of production or emission, methodologies and harmonization of methodologies on risks assessment and management, and any kind of sustainable indicators. The second is the WEO Disputes Settlement Body with a mission of implementing and applying the sustainable indicators measured and adopted by the WEO Scientific Body. This contribution to IEG improvement for more sustainability came to the conclusion that there are enough suitable conditions gathered and assets under UN current scientific activities for these changes to take place. It is therefore on the basis of such a potential to ensure more sustainability at the coming global environmental governance reform that this contribution calls for the political goodwill which is here presented as the main asset of sustainability in IEG.